Integrated coordinated control and optimization of photovoltaic hybrid energy storage for primary frequency regulation - Yang, Peng; Wang, Lei; Zhang, Runtao; Su, Can; Cheng, Ziwei (Frontiers in Energy Research, 2025)
Large-scale photovoltaic (PV) integration into microgrids often leads to reduced inertia, diminished damping, and increased generation intermittency. To address these challenges, this paper proposes a coordinated control and optimization strategy for PV–hybrid energy storage systems. An inertia coefficient k, derived from the energy equivalence between the rotational kinetic energy of a synchronous generator and the stored energy of batteries, is introduced. An optimized inertia control scheme is designed to suppress low-frequency load fluctuations based on microgrid frequency variations, thereby mitigating disturbance-induced frequency deviations, while a supercapacitor voltage-deviation control loop is incorporated to attenuate high-frequency load fluctuations and stabilize DC bus voltage. An optimization model targeting improved dynamic frequency response stability is then formulated and solved using a multi-objective design approach based on an improved particle swarm optimization (PSO) algorithm, with feasible steady-state initialization ranges specified for key parameters. MATLAB/Simulink simulations under scenarios of sudden load increase, continuous load variation, and low-inertia supercapacitor operation demonstrate that the proposed method outperforms conventional control strategies by reducing frequency excursions, lowering the rate of change of frequency (RoCoF), improving the frequency nadir, providing virtual inertia, and enhancing overall system stability.